Twenty-Four-Hour Intraocular Pressure Control with Omidenepag Isopropyl 0.002% in Patients with Glaucoma and Ocular Hypertension - Shiratori N (Dove Medical Press, 2021)
Naka Shiratori,1,2 Yusuke Nishio,1,2 Ayaka Takeda,1,2 Shio Sugimoto,1,2 Kenji Takazawa,2 Naomi Otsuka,3 Naruhiro Ishida,3 Daisuke Shii,3 Kiyotaka Hori,3 Kenji Nakamoto1 1Department of Ophthalmology, Nippon Medical School, Tokyo, Japan; 2Shinanozaka Clinic, Tokyo, Japan; 3Japan Medical Affairs Group, Santen Pharmaceutical Co. Ltd., Osaka, JapanCorrespondence: Naka ShiratoriDepartment of Ophthalmology, Nippon Medical School, 1-1-5 Sendagi, Bunkyo-ku, Tokyo, JapanTel +81-3-3822-2131Fax +81-3-5685-0988Email shiratori@nms.ac.jpPurpose: To clarify the intraocular pressure (IOP)-lowering effect of a selective prostanoid EP2 receptor agonist, omidenepag isopropyl (OMDI) during a 24-hour period.Patients and Methods: Subjects aged ≥ 20 years and with diagnosed, untreated primary open-angle glaucoma or ocular hypertension were enrolled. IOP measurements were performed every 4 hours over a 24-hour period using a Goldmann applanation tonometer (GAT) and Icare PRO tonometer (PRO). The baseline 24-hour IOP was measured in untreated subjects. After the baseline measurements, participants were given OMDI 1 drop once daily at night for 4 weeks. At week 4, the IOP measurement was repeated under the same conditions. Diurnal (9 am, 1 pm, 5 pm) and nocturnal (9 pm, 1 am, 5 am) IOP measurements were compared between baseline and treatment with OMDI. Safety measures included adverse events, slit-lamp biomicroscopy, visual acuity, heart rate and blood pressure.Results: Of 27 participants enrolled, 25 patients (20 males and 5 females, average age 52.2 ± 8.5 years) completed the study. In the sitting position, the baseline diurnal and nocturnal mean IOPs (GAT) were 19.1 ± 2.1 mmHg and 18.2 ± 2.6 mmHg, respectively, the diurnal and nocturnal mean IOP reduction from baseline were – 2.8 ± 2.6 mmHg (p < 0.0001) and – 3.3 ± 2.9 mmHg (p < 0.0001), respectively, mean 24-hour IOP (GAT) was significantly lower with the OMDI treatment (− 3.1 ± 2.5 mmHg, p < 0.0001). In the supine position, the baseline nocturnal mean IOP (PRO) was 17.99 ± 2.22 mmHg, and the nocturnal mean IOP reduction from baseline was − 1.78 ± 2.37 mmHg (p = 0.0009) after 4 weeks of the treatment. Nine adverse events were observed in 8 patients including mild conjunctival hyperemia (n = 8) and mild iritis (n=1). There were no significant effects on systemic safety.Conclusion: Once daily OMDI treatment was able to produce stable 24-hour IOP reduction.Keywords: omidenepag isopropyl, prostanoid EP2 agonist, 24-hour IOP control